Meta-analysis of average change in laboratory-measured HbA1c among people with type 1 diabetes mellitus using the 14 day Flash Glucose Monitoring System. (June 2020) - Gordon, Ian; Rutherford, Carolyn; Makarounas-Kirchmann, Kelly; Kirchmann, Matt
Abstract: Aim: FreeStyle Libre™ Flash Glucose Monitoring System (Flash GM), a novel, sensor-based, factory-calibrated system has been compared with self-monitoring of blood glucose in a well-controlled adult type 1 diabetes mellitus (T1D) population (HbA1c ≤ 7.5%, 58 mmol/mol), in a randomized controlled trial (RCT). The need for RCTs to recruit homogenous patients and for a well-controlled environment may not necessarily reflect use of a new technology in real clinical practice. Methods: A random effects meta-analysis of all identified studies in T1D was performed to investigate changes in laboratory-measured HbA1c following introduction of Flash GM. Results: Flash GM introduction showed a mean change from baseline to longest follow-up timepoint of −0.41% ([95% CI −0.51%, −0.31%]; P < 0.001; −4.5 [95% CI −5.6, −3.3] mmol/mol) in HbA1c in the random effects meta-analysis (34 studies comprising 5, 466 participants). When the Flash GM arms of the two RCTs were excluded, there was a similar change in HbA1c of −0.41% ([95% CI −0.50%, −0.32%], P < 0.001; −4.5 [95% CI −5.4, −3.5] mmol/mol) in the 32 uncontrolled studies. Considerable heterogeneity was shown in all meta-analyses (I 2 values > 85%), likely due to the inclusion of diverse populations and variations in study protocols, meaning random effects meta-analyses should be strongly preferred. Conclusions: In people with T1D, use of Flash GM for 2 to 24 months was associated with an estimated HbA1c reduction from baseline of 0.4%. A similar reduction occurred in uncontrolled studies where baseline HbA1c was generally higher compared with Flash GM arms of well-controlled studies.